ANALYSIS OF MAJRUR ISIM-ISIM IN SURAH AL-MULK (Karya Ilmiah Mahasiswa (KIMA), 2022)
After the researchers conducted research and discussion of the various jar letters in surah al-Mulk based on the description and analysis of the data obtained from observation and documentation studies, it can be developed through several conclusions, namely the ism that is read jar because of the inclusion of the jar letters in sura al-mulk There are 79 data, namely 5 letters in jar 'ala, 9 letters in jar lam, 12 letters in jar fii, 9 letters in jar min, 12 letters in jar ba', 4 letters in jar ila, 6 isim that follow the previous word, and 23 isim majrur because it starts with isim nakirah (mudhof ilaihi). Researchers realize that the writing of the results of this thesis research still needs further development so that it can become better writing.